Latino college presidents in their own words - León, David J. (David Jess); Martinez, Ruben Orlando (Bingley, U.K. : Emerald, 2013)
Latino college presidents : in their own words is a collection of autobiographical-professional essays by leading Latino and Latina presidents of colleges and universities across the country. Each has written a chapter based on their personal education and professional lives. The presidents divide their essays into three sections: 1) Surviving the educational pipeline to obtain an advanced degree, in which they detail their parents' support and at times sacrifices for their children's educational dreams; 2) Moving up the faculty/administrative ladders, in which they cite challenges they experienced and numerous examples from their backgrounds that helped them become successful professors and administrators; 3) Advice for up-and-coming administrators, in which they describe numerous projects they designed and implemented, often reflecting their parents' values and impact on their long careers.
Introduction : Coronando La Academia / Rubén O. Martinez, David J. León -- The status of Latino presidents in U.S. public higher education / David J. León, Rubén O. Martinez -- Shifts happen : the journey of a Latina college president / Erlinda J. Martinez -- Career path of a Latina college president / Herlinda Martinez Glasscock -- A lonely road to the presidency / Leslie Anne Navarro -- Chicano college presidents : the role of the college in community transformation / Monte E. Perez -- Leadership perspectives: from migrant fields to the presidency / Rodolfo Arévalo -- The road to college president : an unconventional journey / Ricardo R. Fernández -- Lessons in leadership : how experiences and values have shaped my presidency / William V. Flores -- Staying in school - forever : from student to president / Mildred García -- The university presidency and public higher education in a changing and diverse America : a California story / Alexander Gonzalez -- On becoming a university president : a Latino perspective / Ricardo Romo -- Two roads converge / Francisco G. Cigarroa -- Conclusion : future climbers : lessons learned and final thoughts / Rubén O. Martinez, David J. León.
Includes index.
Print version record
Keywords: Company secretary: role & responsibilities; Boards & directors: role & responsibilities; Hispanic American college presidents -- United States -- Biography; Education, Higher -- United States